2020
DOI: 10.24057/2071-9388-2020-12
|View full text |Cite
|
Sign up to set email alerts
|

Hazardous Ice Phenomena In Rivers Of The Russian Arctic Zone Under Current Climate Conditions And The Safety Of Water Use

Abstract: The ice regime of the Russian Arctic rivers and its hazardous manifestations under current climate conditions are characterized. The ice phenomena in rivers in the region determine the conditions of navigation, water supply, hydropower station (HPS) operation, and the construction of temporary ice bridges and roads. Data of more than 100 hydrological gages over period from 1936 to 2016 were used to compile various cartographic materials and to analyze the spatial variations of the dates of ice phenomena, the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
2
6
0
Order By: Relevance
“…The same direction of shift was also observed over other SGRs on the Kolyma River (Site ID 1757, 1758) resulting in a shorter duration of river ice cover. The tendency to later freeze‐up on the River Yenisey observed by Agafonova and Vasilenko (2020) is consistent with SMOS based results (Site ID 89) as well.…”
Section: Comparison To Previous Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The same direction of shift was also observed over other SGRs on the Kolyma River (Site ID 1757, 1758) resulting in a shorter duration of river ice cover. The tendency to later freeze‐up on the River Yenisey observed by Agafonova and Vasilenko (2020) is consistent with SMOS based results (Site ID 89) as well.…”
Section: Comparison To Previous Resultssupporting
confidence: 90%
“…The same direction of shift was also observed over other SGRs on the Kolyma River (Site ID 1757, 1758) resulting in a shorter duration of river ice cover. The tendency to later freeze-up on the River Yenisey observed by Agafonova and Vasilenko (2020) is consistent with SMOS based results (Site ID 89) as well. Vuglinsky and Valatin (2018) Other papers by Grześ and Ćmielewski (2008) as well as Smith (2000) study apparent trends in river ice events and ice cover changes from databases gathered at the U.S. National Snow and Ice Data Center.…”
Section: Comparison To Previous Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…However, in the southern part of the region, the ice thickness is 0.07 to 0.20 m less than that in the north. Climate change has affected river ice in the Canadian Arctic (Prowse et al, 2011a, b) and the European part of Russia (Agafonova and Vasilenko, 2020). Mann-Kendall tests performed on the ice time series with complete records (Polnovat, Gorki and Muzhi; see Table 1) have revealed that ice onset had occurred significantly later (0.05 level) only at the Polnovat station.…”
Section: In Situ Data and Ice Regime At Studied River Reachesmentioning
confidence: 99%